Stock assessment of Penaeus spp. off the east coast of India - Rao, G Sudhakara; Subramaniam, V Thankaraj; Rajamani, M; Manickam, P E Sampason; Maheswarudu, G (Indian Journal of Fisheries, 2011)
Penaeid prawn Sandingi increased from 20 744 tonnes in 1980 to 37 410 tonnes in 1986 and thendeclined to 31 029 tonnes in 1989 (average 29 642 tonnes), Prawns of the genus Penaeus supportedgood fishery all along the east coast of India forming 40% of the penaeid prawn landings. lite threecommercially important species, viz. Penaeus indicus, P. semisulcatus and P. monodon, contributed5 849, 4 387 and 639 tonnes, respectively, to the annual penaeid prawn landings of the east coast.Tamil Nadu with annual landings of 7 880 tonnes was the major contributor to the Penaeus landingsof the east coast followed by Andhra Pradesh (1 639 tonnes), Orissa (387 tormes), Pondicherry (119tonnes) and large trawlers (850 tonnes). Past work on biological aspects such as postlarval immigration,juvenile emigration, i'ood and feeding habits and maturation and spawning has been reviewed. Age andgrowth parameters of P.indicus and P. semisulcatus were estimated by employing ELEFAN I method.Population estimates of P.indicus and P. semisulcatus showed very high fishing mortality and decliningyidd while those of P. monodon indicated scope for increasing the landings. HSY estimates for P.indicus, P. semisulcatus and P. monodon are S 961 tonnes, 4 681 tonnes and 652 tonnes respectively.Species-wise and state-wise catch quotas have been suggested based on MSY and the present landings.